LEARNING INDICATORS OF COOPERATIVE MANAGEMENT IN THE REVIEW OF THE ECONOMIC PERSPECTIVE - Futum Hubaib (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
The background of the research is to see and examine the economic wheels of the citizens, which in part seems to still have to struggle in carrying out the economic sufficiency of their families, and the purpose of the research is, to provide a solution, how to make a good system in managing a cooperative management system, as an alternative. which need to be studied and studied in a comprehensive manner is, the economic implementation of the cooperative model, around our citizens need to be encouraged, in all fields of life. In this study the authors made a personal approach to the participants, with descriptive qualitative case study models, and this research was conducted with involving 15 participants, for about 14 weeks. The results of this study indicate a significant change in the participants, especially in the field of transactions or purchases, all kinds of their needs